A Retrospective Observational Study Of Eeg Findings in a Tertiary Care Hospital, Dhaka, Bangladesh (Bangladesh Journal of Medicine, 2022)
Background: Electroencephalography (EEG) is an electrophysiological observing strategy to record the electrical activity of the brain which is used in a seizure disorder, organicity, and psychiatric conditions. In spite of the overwhelming burden of epilepsy in Bangladesh, there remains a relative scarcity of neurophysiology services and restricted distributed information on electroencephalography (EEG) highlights among the population. The aims of the study to explore the EEG findings of distinctive cases and their associations in various clinical scenarios.Methods: This study was a hospital-based retrospective study on the patients who underwent EEG in the EEG room in the department of Neurology & Medicine in Sir Salimullah Medical College & Mitford Hospital, Dhaka during January 2018 to December 2018. Data were recorded from EEG registers and reports. Data were analyzed utilizing SPSS version 25. Frequency distribution was studied and the Chi-Square test and Logistic Regression were applied for categorical variables.Results: Of the total 245 patients studied, he median age was 10.90 +/- 22.1 years and 53.9% were male. The patient attended for performing EEG the initial clinical diagnosis is not mentioned (64.5%). The commonest reason for EEG referral was to rule out seizure disorder (78.0%), requested mostly from the outpatient department (OPD). EEG abnormality was seen in 35.9% of patients and the site of EEG abnormality in the brain was hemispheric epilepsy (19.2%). The most common type of EEG abnormalities was slow-wave (9.8%). EEG diagnosis was normal (64.5%) most of the patients, whereas the rest of them (35.5%) diagnosed as epilepsy. The EEG abnormality detection rate was significant in those referred from the Department of the out-patient department (OPD) and Neurology.Conclusion: Epilepsy is more common in younger male and the most of the EEG were normal. The commonest type of abnormalities in EEG pattern was slow wave which was hemispheric.Bangladesh J Medicine 2022; 33: 138-144